Fully developed Darcy-Forchheimer mixed convective flow over a curved surface with activation energy and entropy generation. (May 2020) - Muhammad, Riaz; Khan, M. Ijaz; Jameel, Mohammed; Khan, Niaz B.
Highlights: Dissipative mixed convective Darcy-Forchheimer flow over a curved surface is addressed. Ohmic heating and dissipation effects are considered. Binary chemical reaction with activation energy is considered. Numerical results are computed through ND-Solve technique. Abstract: Background: Mixed convection (forced+natural convection) is frequently observed in exceptionally high output devices where the forced convection isn't sufficient to dissipate all of the heat essential. At this point, consolidating natural convection with forced convection will frequently convey the ideal outcomes. Nuclear reactor technology and a few features of electronic cooling are the examples of these processes. Mixed convection problems are categorized by Richardson number (Ri), which is the ratio of Grashof number (for natural convection) and Reynolds number (for forced convection). For buoyancy or mixed convection the relative effect can be addressed by Richardson number. Typically, the natural convection is negligible when Richardson number is less than 0.1 (Ri < 0.1), forced convection is negligible when Richardson number is greater than 10 (Ri > 10) and neither is negligible when (0.1 < Ri < 10). It might be noticed that generally the forced convection is large comparative with natural convection except in case of remarkably low forced flow velocities. The current work gives significant insights regarding dissipative mixed convective Darcy-Forchheimer flow with entropy generation over a stretched curved surface. The energy equation is developed with respect to nonlinear radiation, dissipation and Ohmic heating (Joule heating). Binary reaction via activation energy is accounted. Method: Curvilinear transformations are utilized to change the nonlinear PDE's into ordinary ones. Computational outcomes are obtained via NDSolve MATHEMATICA. The results are computed and discussed graphically. Results: Velocity decays for Forchheimer number. Entropy generation enhances for diffusion parameter and chemical reaction parameter. Concentration profile reduces chemical reaction parameter and enhances for activation parameter.